2021
DOI: 10.3389/fneur.2021.608403
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost, Accurate, Effective Treatment of Hypertensive Cerebral Hemorrhage With Three-Dimensional Printing Technology

Abstract: Background: Hypertensive intracerebral hemorrhage (HICH) is an acute, severe neurosurgical disease. Puncture drainage of the hematoma has gradually been accepted as a surgical treatment for HICH because of its minimally invasive nature. The precision of the puncture is extremely high because of particular physiological functions. This study was performed to explore the effect of a navigation mold created by three-dimensional printing (3DP) technology in the surgical treatment of HICH.Material and methods: We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…3D-printed technololg has been succeeded applied in medical fields such as intraoperative navigation [ 37 ]. Wang et al applied 3D printing navigation for puncture and drainage of PBH in 2020 and found that the actual puncture target was accurately positioned in the hematoma in 7 cases, and the effect was satisfactory.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3D-printed technololg has been succeeded applied in medical fields such as intraoperative navigation [ 37 ]. Wang et al applied 3D printing navigation for puncture and drainage of PBH in 2020 and found that the actual puncture target was accurately positioned in the hematoma in 7 cases, and the effect was satisfactory.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…The common stereotactic methods included the use of frame technology, frameless technology, neuronavigation system, and surgical robot; those greatly improved the accuracy of puncture. 3D-printed technololg has been succeeded applied in medical fields such as intraoperative navigation [37]. Wang et al applied 3D printing navigation for puncture and drainage of PBH in 2020 and found that the actual puncture target was accurately positioned in the hematoma in 7 cases, and the effect was satisfactory.…”
Section: Minimally Invasive Surgery Takahama Et Al Have Firstlymentioning
confidence: 99%
“…However, the success rate is low, and patients with unstable vital signs cannot tolerate this type of surgery. Craniotomy hematoma removal and puncture drainage are the primary surgical treatment used for brain stem bleeding [58,59]. erefore, hematoma puncture and drainage have been increasingly applied for the surgical treatment of intracerebral bleeding due to its minimally invasive nature, low cost, and short operation time [60], especially for patients experiencing severe brainstem hemorrhage.…”
Section: Intracranial Vascular Diseasementioning
confidence: 99%
“…In another study enrolling 37 PPH patients, Hara et al found that 72% (13 of 18) of subjects undergoing CT-guided stereotaxic aspiration showed a dramatic improvement, whereas only 42% (8 of 19) of subjects treated conservatively did (11). The application of three-dimensional (3D) printing technology is achieving great success in various medical fields, including surgical intraoperative navigation (89,90). Recently, Wang et al successfully tested the application of a 3D-printed navigation template for puncture drainage in patients with severe brainstem hemorrhage (78).…”
Section: ) Stereotactic Hematoma Puncture and Drainagementioning
confidence: 99%